THE RELATIONSHIP BETWEEN AN ANXIETY OF MATHEMATICS AND ATTENTION OF PARENTS WITH MATHEMATICS LEARNING OUTCOMES TO THE EIGHTH GRADE STUDENTS - Euis Erni Marlina; Uus Kusdinar (Universitas Ahmad Dahlan, 2018)
Based on the observations at the time at SMP Muhammadiyah Depok Sleman Regency, the anxiety of facing the students â€˜mathematics subjects is still high. This can be seen from the studentsâ€™ attitude that is restless, afraid, worried, anxious, nervous, tense when told that there will be a daily test, pretest And posttest math lessons, as well as some poor parental concerns that are based on some parents who not come to school to take care of education issues. This study aims to determine whether or not there is a significant relationship between the anxiety of facing mathematics students and attention of parents of VIII class at SMP Muhammadiyah 1 Depok Sleman Semester Even semester In Academic Year 2016/2017. This study population is all the student's VIII Class of SMP Muhammadiyah 1 Depok semester of academic year 2016/2017. It is taken in VIII B Class as the sample of research class with a random sampling technique to the class. Data collection techniques in the form of test techniques and questionnaires. The research instrument test uses validity tests, different power tests, and reliability tests. Test prerequisite analysis includes a normality test, independent test, linearity test. Analysis of data for hypothesis testing using correlation analysis and linear regression analysis.Â The results showed that there was no negative and significant relationship between anxiety facing mathematics subjects with mathematics learning result, with r = -0,0081, there is a positive and significant correlation between the attention of parents with the results of learning mathematics, with r = 0,6093, and there is a significant relationship between the anxiety of facing mathematics subjects and the attention of parents with the results of learning mathematics, with so that . Relative contribution of X1 = , X2 = 99,746%, and effective contribution X1 = %, X2 = %. This indicates that the attention of parents (X2) has a greater relationship with mathematics learning outcomes than with anxiety facing Mathematics subjects (X1) with mathematics learning outcomes.